Hahnemann's legacy - Barthel, P. (British Homeopathic Journal, 1992)
When Hahnemann published the provings of Bryonia alba in the first edition of the Materia Medica Pura, he knew exactly which species of Bryonia he had been using. After his death, the plant gradually came to be replaced with another species of the same genus, with no distinction made and the second species practically unproven.Today, Bryonia dioica, a practically unproven species, is widely sold as ‘Bryonia’, and customers are not informed about this inadmissible exchange. Hahnemann made it very clear that every plant species is unique and cannot be exchanged for any other.At the same time his improvements to the manufacturing process, based on experience, have not been adopted by pharmaceutical firms, nor in the German Homoeopathic Pharmacopoeia (GHP). Instead, they have been adopting less labour intensive methods, though these have not been properly validated.
Keywords: Bryonia alba; Bryonia dioica; Drug provings; Quality of medicines